Directors' Cost Allocation in Construction Firm Common Method and AI Method A Case Study of PT WZK - Buana, Mohamad Torik Langlang; Sriyanto, Agus; Sinambela, Tongam; Tarmidi , Deden; Sapian, Safeza Mohd (Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze how directors' costs are allocated in a construction services firms. The number of contractors in the country has boasted over 200,000 entities in the last three years, to support the Indonesian government's current focus on infrastructure development. In turn, these companies’ success is strongly led by their board of directors. The board of directors’ costs in a construction services company are charged to each project using systematic methods to ensure fair allocation. The study employed qualitative methods using a case study of a road construction firm that handles several projects every year. The result of the study found that the firm had a good understanding of management accounting methods and an effective computer accounting system, enabling fair directors’ cost allocation. The findings are significant to be used for reference to management accountants in construction services companies.